2020
DOI: 10.1111/plb.13143
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid and hydrogen peroxide are involved in drought priming‐induced drought tolerance in wheat (Triticum aestivum L.)

Abstract: Drought is one of the major stress factors in wheat production on a global scale. Drought priming during the early growth stage can enhance drought tolerance in wheat (Triticum aestivum L.). Abscisic acid (ABA) and hydrogen peroxide (H2O2) are important signal molecules in the adaptation of plants to drought stress. However, the roles of ABA and H2O2 in drought priming‐induced drought tolerance are not clear. In the present study, we evaluated the responses of wheat to an ABA inhibitor, H2O2 scavenger and an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…The expression of the proline synthesis related enzyme Δ1‐pyrroline‐5‐carboxylate synthetase ( P5CS ) and of proline dehydrogenase ( PDH ) was in line with the proline content in the treatments of primed plants (Figure 6). Our previous study found that ABA is required for drought priming induced osmolyte accumulation and that inhibitors of ABA biosynthesis suppressed drought priming induced osmolyte accumulation (Wang, Li, et al., 2020; Wang, Zhang, et al., 2020). Here, the contents of osmolytes were in agreement with the contents ABA and NO, but not with NR activities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression of the proline synthesis related enzyme Δ1‐pyrroline‐5‐carboxylate synthetase ( P5CS ) and of proline dehydrogenase ( PDH ) was in line with the proline content in the treatments of primed plants (Figure 6). Our previous study found that ABA is required for drought priming induced osmolyte accumulation and that inhibitors of ABA biosynthesis suppressed drought priming induced osmolyte accumulation (Wang, Li, et al., 2020; Wang, Zhang, et al., 2020). Here, the contents of osmolytes were in agreement with the contents ABA and NO, but not with NR activities.…”
Section: Discussionmentioning
confidence: 99%
“…Heat priming or treatment with NO donor and H 2 O 2 increased wheat seedlings resistance to heat‐damage, while scavengers of NO (c‐PTIO) and H 2 O 2 (DMTU) inhibited the heat‐resistance induced by heat priming, suggesting a crosstalk between NO and H 2 O 2 (Karpets et al., 2015). Our previous study showed that drought priming during an early stage induced the tolerance to drought occurring at a later growth stage and that H 2 O 2 mediates abscisic acid (ABA) involved in drought priming, thereby contributing to drought tolerance in wheat (Wang, Li, et al., 2020; Wang, Zhang, et al., 2020). In this study, scavenging of H 2 O 2 and NO followed by drought priming significantly increased the relative electrical conductivity in the primed plants under drought stress in wheat seedlings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2019; Wang et al . 2020). Tall fescue ( Festuca arundinacea ) is one of the most widely used cool‐season grass species as forage and turf and is sensitive to heat stress, with loss of forage yield and turf quality during summer months (Wang et al .…”
Section: Introductionmentioning
confidence: 99%